The Effect of Work Discipline and Work Motivation on Employee Productivity with Competence as Interviening Variables - Marlapa, Eri; Mulyana, Bambang (International Review of Management and Marketing, 2020)
Companies must pay attention to the ability of employees, payback to employees, sanctions against discipline violations, tighter supervision in an effort to improve or improve employee performance. Work discipline is an important factor in improving employee performance. With good work discipline from employees such as arriving on time, carrying out work in accordance with what has been set by the company, obeying company regulations will be able to improve the performance of these employees so that company targets will be achieved.The purpose of this study was to determine the effect of work discipline and work motivation on employee productivity with competence as an interviening variable at PT. Denso Indonesia Plan 2 Cibitung Bekasi Jawa Bara. This research uses the type of research kquantitative research. This research was conducted at PT. Denso Indonesia Plan 2 Cibitung Bekasi West Java, with a population of 192 employees. In this study a sample of 130 people with a tolerance limit of 5%. The sampling technique used in this study is the Purpose Sampling technique to determine the research sample with certain considerations aimed at making the data obtained later more representative. As for the sample is a production employee who has worked for more than 3 years and worked as a machine operator. Test the validity and reliability of the data using the product moment correlation formula from Pearson and Cronbach’s Alpha. Data analysis techniques used to test hypotheses are multiple linear regression analysis and Path analysis. Keywords: Work Discipline, Work Motivation, Employee Productivity, Competence JEL Classifications: J24, J81, L2 DOI: https://doi.org/10.32479/irmm.9922